Incremental value of early systolic lengthening and postsystolic shortening in detecting left anterior descending artery stenosis using nonstress speckle-tracking echocardiography - Takako Ishigaki; Toshihiko Asanuma; Noriaki Yagi; Hiromi Izumi; Shoko Shimizu; Yoshihisa Fujisawa; Toshiyuki Ikemoto; Ryoji Kushima; Kasumi Masuda; Satoshi Nakatani (Scientific Reports, 2021)
Abstract The diagnosis of coronary artery disease (CAD) with nonstress echocardiography remains challenging. Although the assessment of either early systolic lengthening (ESL) or postsystolic shortening (PSS) allows the sensitive detection of CAD, it is unclear whether the integrated analysis of ESL and PSS in addition to the peak systolic strain can improve the diagnostic accuracy. We investigated the incremental value of ESL and PSS in detecting left anterior descending artery (LAD) stenosis using nonstress speckle-tracking echocardiography. Fifty-nine patients with significant LAD stenosis but without visual wall motion abnormalities on echocardiography at rest (30 single-vessel stenosis, 29 multivessel stenosis) and 43 patients without significant stenosis of any vessel were enrolled. The peak systolic strain, the time to ESL (TESL), and the time to PSS (TPSS) were analyzed in all LAD segments, and the incremental values of the TESL and TPSS in detecting LAD stenosis and the diagnostic accuracy were evaluated. In the apical anterior segment, the peak systolic strain was significantly lower and TESL and TPSS were significantly longer in the single-vessel group than in the no stenosis group. In the single-vessel group, the addition of TESL and TPSS to the peak systolic strain significantly increased the model power in detecting stenosis, and the integrated analysis improved diagnostic accuracy compared with the peak systolic strain alone. In contrast, this incremental value was not demonstrated in the multivessel group. The integrated analysis of the peak systolic strain, ESL, and PSS may allow better screening of single-vessel LAD stenosis using nonstress speckle-tracking echocardiography.